Legal Sanctions for Notaries Violating the Code of Ethics in Making Deeds in Indonesia - N Saly, Jeane; Eka Putri, Amanda Fitriani; Mariana Sitorus, Lena; Michellena, Michellena; Syamila, Najma; Ayu Puspita, Salsabillah (IAIN Langsa, 2023)
The authority of notaries in Indonesia is regulated by Law Number 2 of 2014 concerning Notary Positions (UUJN). UUJN was established to ensure that notaries carry out their professional duties by providing legal protection and certainty to the public. However, the implementation of this law has not been optimal, leading to violations that contradict its provisions. In the year 2022, 67 notaries were suspected of violating the code of ethics.Through normative legal research, it was identified that notarial code of ethics violations, such as failure to read out deeds or allowing others to sign deeds in the presence of their staff, have been on the rise. Therefore, there is a need for the optimization of sanctions against notaries who breach the code of ethics, both in civil and criminal aspects, in accordance with the severity of their offenses.Supervision of notaries aims to ensure compliance with existing regulations and the code of ethics. If proven guilty of violations, notaries should face sanctions commensurate with their transgressions. The Notarial Code of Ethics encompasses five levels of sanctions, ranging from warnings to dishonorable discharge from the Notary Association membership. Notaries are obligated to adhere to UUJN, the Notarial Code of Ethics, and maintain integrity and dignity in the execution of their profession.